MEMBANGUN DATA WAREHOUSE UNTUK MENGANALISA POLA SISWA YANG MENDAFTAR DI ITENAS. (Studi Kasus Institut Teknologi Nasional Bandung) - Reysandi Alexandria Rifky; Mira Musrini B; Nur Fitrianti F (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
Information is indispensable at this time and with advances in technology, the need for accurate information in everyday life can be obtained easily. So that data information can be categorized as an important element in current and future developments. Higher education institutions need data information to make it easier to search and read the required data, and to create a database that can be used to support the analysis process for decision-makers. The large number of student data registering and being accepted at ITENAS in recent years has required the campus to input data on a large scale until it reaches the amount of data. The use of a data warehouse can provide detailed and easier information when required student data information received at itenas based on the amount of data. The results of this study will produce a data warehouse for the Itenas campus, as well as accurate and useful reports and analysis. The results show the research that Itenas has decreased the number of enthusiasts or students received during the last 4 years, the highest was in 2015, which was 1856 and the lowest was in 2018 as many as 1468 enthusiasts or students accepted. Bandung is also the first city to register, followed by Cirebon in second place